A, Article Paulina et,al: Indonesia - Adinda, Jelita; Irawan, Fajar Awang (Journal of Sport Science and Education, 2022)
The purpose of this study was to analyze the suitability of the squatting position pointing motion in athletes in Semarang Regency. This type of research is purposive sampling, namely the technique of determining the sample with certain considerations. The method in this research uses descriptive analysis. The results of the analysis of the pointing motion of athletes in Semarang Regency, there were 11 boys and girls, each pointing stage in the kinematic data: 1) time, 2) right arm flexion angle, 3) right knee flexion angle, 4) trunk extension angle 5) extension angle backswing 6) wrist release extension angle 7) ball height. The total number of 11 research samples entered in the "appropriate" category. The motion suitability assessment analysis was carried out by 1 regional license trainer, and using the dartfish analysis software application version 8.0. The conclusion of this study shows that the analysis of the suitability of the pointing motion of the squatting position is in the "appropriate" category. Future research is expected to be able to examine the kinetic data to complement this research data